GARNET: An Edge Virtualized Everything Function Management Architecture - Cunha, Hugo Gustavo Valin Oliveira da (2021)
The Internet of Things represents a comprehensive environment that connects a large number of heterogeneous physical objects, such as appliances, facilities, animals, vehicles, farms, factories, etc., to the Internet to increase the efficiency of applications such as logistics, manufacturing, agriculture, urban computing, home automation, assisted living and various real-time computing applications.While Cloud Computing has been a key enabling technology for the Internet of Things, a small increase in the percentage of cyber-physical or connected objects represents a dramatic shift in the computing resource space and a potential tsunami of hyper-connectivity. Today's infrastructure will struggle to accommodate historic levels of service quality. Multi-Access Edge Computing bridges the gap between cloud and Internet of Things devices, enabling computing, storage, networking and data management on network nodes close to the end devices. Network Function Virtualization transitions network service functions from hardware to software. Together, Multi-Access Edge Computing and Network Functions Virtualization provide an effective solution for modern computing, ensuring speed and reliability for end-users. One benefit of using both technologies is the combination of scalability and low latency. Multi-Access Edge Computing plays a significant role in alleviating and solving network demands such as the Internet of Things. Therefore, the main objective of this work is to propose and evaluate an architecture compatible with the ETSI Management and Orchestration software stack for managing virtualized functions in Multi-Access Edge Computing deployed in low-cost devices and bare metal servers in an integrated way, that offers unified native monitoring from hardware to services.